Effect of processing parameters on flexural properties of 3D‐printed polyetherketoneketone using fused deposition modeling. Issue 2 (21st November 2020) - Xu, Chen; Cheng, Kangjie; Liu, Yunfeng; Wang, Russell; Jiang, Xianfeng; Dong, Xingtao; Xu, Xu
Abstract: Polyetherketoneketone (PEKK) is an engineering plastic with ultrahigh mechanical performance and has attracted considerable attention in the medical and technical fields. Printing parameters during fused deposition modeling (FDM) for PEKK have a significant impact on final part quality. In this study, a relationship between the process parameters and flexural properties of PEKK was investigated by conducting three‐point bending tests, and scanning electron microscopy was employed to analyze the microstructure of fracture surfaces. Nozzle temperature, layer thickness, and infill density affected flexural properties by changing the porosity and interlayer bonding strength. Interlayer separation is the main failure mode of the upright orientation samples, while intralayer failure is likely to occur in the on‐edge orientation samples. The flexural properties of FDM‐printed PEKK under optimum parameters are comparable to those of mandibular bones, indicating that PEKK is a potential candidate for repairing mandibular defects. The results highlighted in this study are fundamental to the optimal design of complex ultralight, highly efficient structures. Abstract : Comparison of flexural properties between PEKK and mandibular bone after optimizing printing parameters.